2021
DOI: 10.3390/buildings11120589
|View full text |Cite
|
Sign up to set email alerts
|

Plan for the Sustainability of Public Buildings through the Energy Efficiency Certification System: Case Study of Public Sports Facilities, Korea

Abstract: This study examines strategies for energy efficiency in public buildings in Korea and the implementation of certification systems. It also identifies the actual plan status and discusses improvements at the institutional level. The target is the national sports centers, where the discussion on energy efficiency has been assiduous, as they have recently expanded regionally in Korea. Among the 541 national sports centers in Korea, 90 facilities for which a preliminary review was performed on the plan by the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Walls et al [49] have shown that in the residential sector, there is evidence that people are not willing to pay a high premium, as they do not see the cost saving benefits. In Korea, Baek [50] found that the government's publicity and initiatives are critical to promote sustainable building development.…”
Section: The Role Of Disclosure Laws and Energy Ratings On Green Buil...mentioning
confidence: 99%
“…Walls et al [49] have shown that in the residential sector, there is evidence that people are not willing to pay a high premium, as they do not see the cost saving benefits. In Korea, Baek [50] found that the government's publicity and initiatives are critical to promote sustainable building development.…”
Section: The Role Of Disclosure Laws and Energy Ratings On Green Buil...mentioning
confidence: 99%
“…It is assumed that the input of the i th node of public sport facility resources is represented by II. It is necessary to calculate the relationship between the associated sport facility nodes and the relationship between configuration and management unit nodes [ 25 ]. The calculation results are shown in the following formula.…”
Section: Resource Allocation and Management Algorithm Analysis Of Pub...mentioning
confidence: 99%
“…Nowadays, the construction industry has made obvious achievements both in terms of construction technology and the total value of construction. As a place for people's daily activities and work, public building facilities are increasing [1].Public buildings can bring great convenience to People's Daily life, thus promoting economic development, but there will also be problems in the practical application process.For example, the energy consumption of public buildings is high and the functionality of some buildings is poor [2].…”
Section: Introductionmentioning
confidence: 99%